Evaluation of Developing Net Zero Energy Buildings in Northern Cyprus - Mahdi, Bavafa (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
In 21th century, the topics of energy and relevant issues involved the different sectors with several challenges. In past years, advent of greenhouse gas emission from consumption of fossil fuels in building sector, showed the importance of optimizing energy use in this sector more than every time. It is estimated that, energy consumption in building sector is growing up by growth in population and increasing for building demand. Hence, approaching sustainable and efficient residential and commercial buildings has been a priority for energy policy makers. Recently, building community is aimed to develop Net Zero Energy Buildings as much as it is possible. Net Zero Energy Buildings accepted as efficient buildings, which are smart choice to reduce energy consumption while maximizing comfort for occupants. Northern Cyprus is almost completely dependent on hydrocarbon fuels to cover energy requirements. On the other hand, Mediterranean climate conditions caused, buildings demand a significant share of energy to meet their heating and cooling loads. The concept of Net Zero Energy Buildings might be effective to modify energy consumption pattern. Hence, this study attempts to evaluate developing of Net Zero Energy homes and is purposed to provide strategies and guidelines with special focusing on utilization of PV panels to achieve Net Zero Energy homes in Northern Cyprus.

ÖZ: 21.yüzyılda,enerji konuları ve bununla ilgili meseleler,farklı sektörleri çeşitli güçlüklerle karşı karşıya bırakmıştır.Geçmiş yıllarda,bina sektöründeki fosil yakıtların tüketimi sırasında ortaya çıkan sera gazı emisyonu, bu sektördeki enerji kullanımını etkili kılmanın her zamankinden daha önemli olduğunu göstermiştir.Bina sektöründeki enerji tüketiminin,nüfusun çoğalması ve artan bina taleplerine paralel olarak arttığı tahmin edilmektedir.Bu yüzden, sürdürülebilir ve enerji verimligi olan konut ve ticari binalar, enerji sektörünun politika yapıcıları tarafından öncelik kazanmıştır. Son zamanlarda, Binalar Cemiyeti, net sıfır enerji binaları mümkün olabildiğince geliştirmeyi amaçlamıştır.Net Sıfır Enerji binalar, enerji tüketimini azaltan ve oturanların rahatını en üst düzeyde tutan verimli binalar olarak kabul edilmiştir. Kuzey Kıbrıs, enerji ihtiyaçlarını karşılamak için hidrokarbon yakıtlara neredeyse tamamen bağlıdır.Bunun dışında,Akdeniz iklim koşulları ; binaların,ısıtma ve soğutma ihtiyaçlarını karşılamak için önemli oranda enerji paylaşımı talebine yol açmıştır. Net Sıfır Enerji Bina kavramı, enerji tüketimi modelini değiştirmek için etkili olabilir. Bundan dolayı bu çalışma; Net Sıfır Enerji evleri geliştirmenin değerlendirmek için bir girişim ve Kuzey Kıbrıs’ta Net Sıfır Enerji evler elde etmek için bir taslak ve de bunu başarmak için PV panellerin kullanımı üzerine odaklanan stratejiler ve yönergeler sağlamayı amaçlamıştır.
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2015. Supervisor: Assist. Prof. Dr. Ercan Hoşkara.
Keywords: Architecture; Architecture and energy conservation; Net Zero Energy Buildings; renewable energy; Energy efficiency; Buildings - Energy conservation - Solar Energy - Cyprus, North